Hakikat Menampakkan Amalan Sedekah dalam Perspektif Tafsir al-Qurthubi - Falah, Muhammad Zulfikar Nur (Jurnal Riset Agama, 2023)
This study aims to analyzes the nature of showing the practice of charity in QS. al-Baqarah [2]: 271 from the perspective of tafsir al-Qurtubi. The discussion of alms is inseparable from the process of showing the practice, while tafsir al-Qurtubi draws into an important pattern of analysis of Islamic law. This research uses library research method, with relevant data sources such as books, journals, theses, theses, dissertations, and so on. This study provides results that in the perspective of al-Qurtubi's interpretation, the interpretation of QS. al-Baqarah [2]: 271 is interpretatively opened by al-Qurtubi with the agreement of the jumhur regarding the law of charity is sunnah. Based on the main context of the text, two things can be concluded. First, the meaning behind showing the practice of charity in the obligatory category is an effort to expect His pleasure. Second, the meaning behind displaying charitable deeds in the sunnah category is to be pure from riya' behavior.